Hospital infections and antimicrobial use: Integrative review on epidemiology and bacterial resistance (Research, Society and Development, 2025)
Introduction: Hospital infections associated with bacterial resistance represent a major challenge in public health, driven by the high mutation capacity of microorganisms and the indiscriminate use of antibiotics, which contribute to the emergence of multidrug-resistant strains and increased clinical complications. Objective: This study aimed to carry out a survey, through an integrative review based on scientific articles published in the last five years, of the main antibiotic-resistant bacteria, highlighting their epidemiological profiles and the most prevalent infection sites. Method: Searches were conducted in the SciELO, PubMed, and CAPES Periodicals databases, using descriptors in Portuguese and English related to bacterial resistance and antibiotic use, considering the period from 2020 to 2025; after removing duplicates and applying inclusion and exclusion criteria, the studies were organized according to author, objective, method, and main results. Results: Of the 33 articles found, 21 met the criteria and indicated that infections caused by multidrug-resistant bacteria such as Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa increase hospitalization time, raise the risk of severe complications, and expand hospital costs due to prolonged treatment needs. Conclusion: The findings reinforce that bacterial resistance exacerbates the impact of hospital infections and highlight the importance of strengthening infection control measures, promoting the rational use of antimicrobials, and intensifying epidemiological surveillance to reduce the spread of multidrug-resistant strains and ensure greater patient safety.